2022
DOI: 10.1021/acs.jafc.1c07323
|View full text |Cite
|
Sign up to set email alerts
|

Click Isotope Mass Probe for Highly Selective Determination of Trace Steroid Hormones in Food Samples

Abstract: Matrix effects are a great challenge for the quantitative analysis of complex food samples by liquid chromatography-tandem mass spectrometry analysis (LC-MS/MS). Stable isotope labeling (SIL) has been widely used as an effective strategy to eliminate matrix effects. Herein, a copper­(I)-catalyzed azide-alkyne cycloaddition (CuAAC) click-reaction-based SIL method was proposed for a highly sensitive and selective determination of six synthetic steroid hormones in three different food samples (milk, yogurt, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Endocrine disrupting steroid hormone residues in food, mainly including sex steroid hormones and adrenocortical hormones, have emerged as a serious risk to human health in recent decades. , It has been reported that excess steroid hormones illegally added to animal feed might remain in animal tissues due to their inherent lipophilic property. These compounds are likely to be transferred and accumulated into the human body via the food chain, resulting in various diseases like osteoporosis, cardiovascular diseases, immune/inflammatory diseases, and breast, ovarian, and prostate cancers. In addition, synthetic steroid hormones usually exhibit increased disrupting potency because they bind to hormone receptors with a higher affinity than the natural counterpart, for instance, the binding affinity of synthetic ethinylestradiol (EE2) to the estrogen receptor is 2-fold higher than the natural 17β-estradiol (E2) in humans. , To ensure the health and safety of consumers, it is essential to develop effective analytical methods for determining steroid hormone residues in food samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endocrine disrupting steroid hormone residues in food, mainly including sex steroid hormones and adrenocortical hormones, have emerged as a serious risk to human health in recent decades. , It has been reported that excess steroid hormones illegally added to animal feed might remain in animal tissues due to their inherent lipophilic property. These compounds are likely to be transferred and accumulated into the human body via the food chain, resulting in various diseases like osteoporosis, cardiovascular diseases, immune/inflammatory diseases, and breast, ovarian, and prostate cancers. In addition, synthetic steroid hormones usually exhibit increased disrupting potency because they bind to hormone receptors with a higher affinity than the natural counterpart, for instance, the binding affinity of synthetic ethinylestradiol (EE2) to the estrogen receptor is 2-fold higher than the natural 17β-estradiol (E2) in humans. , To ensure the health and safety of consumers, it is essential to develop effective analytical methods for determining steroid hormone residues in food samples.…”
Section: Introductionmentioning
confidence: 99%
“…The methods for detecting steroid hormones often involved high-performance liquid chromatography coupled with UV detection (HPLC-UV), HPLC coupled with fluorescence detection (HPLC-FLD), , gas chromatography–mass spectrometry (GC-MS), , and liquid chromatography-mass spectrometry (LC-MS). ,, Among them, liquid chromatography-tandem mass spectrometry (LC-MS/MS) technique is a preferred choice for steroid hormones analysis since it possesses higher sensitivity and the ability to qualitatively and quantitatively monitor multiple analytes. ,, However, the poor ionization efficiency of some steroid hormones and their low concentration in real samples have significantly restricted the sensitivity and efficiency of using LC-MS/MS alone. , Recently, the functional group-targeted chemical labeling strategy has been developed, in which many chemoselective probes such as dansyl chloride, ( O -(3-trimethylammoniumpropyl) hydroxylamine) bromide (QAO reagent), 2-fluoro-1-methylpyridinium p -toluenesulfonate (FMPTS), , and Girard P have been used to enhance the responses of steroid hormones in the mass spectrum and further improve their detection sensitivity. The commonly used probes such as dansyl chloride and FMPTS usually serve as a hydroxyl group-targeted probe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The pretreatment method is determined by the state of the sample, mainly including solid-phase extraction (SPE), liquid-phase extraction, liquid–liquid extraction, and their derived extraction methods. 18 For different environmental matrices, researchers have developed a variety of extraction materials for the extraction of steroid hormones combined with gas chromatography-mass spectrometry (GC-MS), 19 high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS), 20 and biosensing technologies. 21 Thus, an efficient pretreatment method is extremely important for the detection of steroid hormones.…”
Section: Introductionmentioning
confidence: 99%